2007
DOI: 10.1111/j.1472-8206.2007.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin antimalarials moderately affect cytochrome P450 enzyme activity in healthy subjects

Abstract: The aim of this study was to investigate which principal human cytochrome P450 (CYP450) enzymes are affected by artemisinin and to what degree the artemisinin derivatives differ with respect to their respective induction and inhibition capacity. Seventy-five healthy adults were randomized to receive therapeutic oral doses of artemisinin, dihydroartemisinin, arteether, artemether or artesunate for 5 days (days 1-5). A six-drug cocktail consisting of caffeine, coumarin, mephenytoin, metoprolol, chlorzoxazone and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 33 publications
1
46
0
Order By: Relevance
“…Choice of substrates is important as they need to be CYP specific with no interactions between any of the substrates in the cocktail. A recent study by Asimus et al (53), investigated the effect of the antimalarial drug artemisinin and its derivatives on the major human CYP enzymes. Asimus et al designed a six drug cocktail study consisting of caffeine, coumarin, mephenytoin, metoprolol, chlorzoxazone and midazolam to assess CYP1A2, 2A6, 2C19, 2D6, 2E1 and 3A4 activity, respectively.…”
Section: Clinical Drug Interaction Studiesmentioning
confidence: 99%
“…Choice of substrates is important as they need to be CYP specific with no interactions between any of the substrates in the cocktail. A recent study by Asimus et al (53), investigated the effect of the antimalarial drug artemisinin and its derivatives on the major human CYP enzymes. Asimus et al designed a six drug cocktail study consisting of caffeine, coumarin, mephenytoin, metoprolol, chlorzoxazone and midazolam to assess CYP1A2, 2A6, 2C19, 2D6, 2E1 and 3A4 activity, respectively.…”
Section: Clinical Drug Interaction Studiesmentioning
confidence: 99%
“…In addition to the autoinduction phenomenon, both QHS and DHA were found to be potent inhibitors of CYP1A2 activity in vitro (Bapiro et al, 2001) and in vivo (Bapiro et al, 2005;Asimus et al, 2007). Taken together, these results showed that QHS drugs may affect cytochrome P450s (P450s) as both inducer and inhibitor, which may compromise the results of P450 activity in vivo.…”
Section: Introductionmentioning
confidence: 68%
“…QHS appears to induce other enzymes including CYP2C19 (Svensson et al, 1998;Mihara et al, 1999; omeprazole as a marker), CYP3A4 (midazolam hydroxylation; Asimus et al, 2007), CYP2A6 (coumarin hydroxylation; Asimus et al, 2008), and glucuronidation (7-hydroxycoumarin glucuronidation; Asimus et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A previously performed in vivo study including 75 Vietnamese subjects showed a significant interindividual variation in the degree of artemisinin-driven induction of several CYP450 enzymes, including CYP3As, the genes which are canonical targets of PXR (1). In the present work, we built upon this study by hypothesizing that specific single nucleotide polymorphisms (SNPs) in PXR might explain the observed interindividual variability in the level of CYP3A induction.…”
mentioning
confidence: 99%